THE IMPACT OF VITAMIN D ON HEPATIC ENZYMES AND NON-ALCOHOLIC FATTY LIVER DISEASE ACROSS–SECTIONAL STUDY - KHAN , AM; KHAN , ZU; BASIT , A; KHAN , MA; ALI , A (Biological and Clinical Sciences Research Journal, 2023)
Non-Alcoholic Fatty Liver Disease (NAFLD) has become increasingly common globally, raising serious concerns for public health. NAFLD is a complex and multifaceted disease that includes a range of liver diseases, such as cirrhosis, non-alcoholic steatohepatitis (NASH), and simple hepatic steatosis. A combination of environmental, metabolic, and genetic factors causes it. Recent data suggests that vitamin D, a fat-soluble vitamin with various physiological roles, may be crucial for liver health and the development of NAFLD. This cross-sectional study aimed to investigate vitamin D’s potential impact on liver function and the development of NAFLD. A Cross-Sectional Study was conducted at the Department of Medicine, MTI, LRH, Peshawar, from August 2019 to January 2020. Participants for this study were selected from the Department of Medicine at MTI, LRH, Peshawar, between August 2019 and January 2020. The study population included individuals with NAFLD identified by laboratory, radiographic, and clinical criteria. Blood samples were taken to measure the serum levels of vitamin D and liver enzymes, such as aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Additional clinical and demographic information was also collected. The average age of the participants in this study was forty years, and there was an equal distribution of genders. Following treatment, the severity of NAFLD significantly decreased. At the beginning of the study, 12.3% of participants had severe steatosis, 40.3% had moderate, and 48.4% had mild steatosis. After treatment, 40.3% of patients had no steatosis, 47.8% had mild steatosis, and 17% had significant steatosis. ALT, ALP, and bilirubin levels showed significant improvements in liver function, with p-values <0.05. While an increase in ALP indicated improved liver function, decreased ALT levels demonstrated reduced liver inflammation. Lower bilirubin levels indicated improved liver health. These findings suggest that treatment, possibly involving vitamin D supplementation, improved liver function and reduced the severity of NAFLD, highlighting the need for further research. This study indicates that vitamin D supplementation may benefit liver function and non-alcoholic fatty liver disease severity. The findings suggest that vitamin D may be a helpful treatment option for managing NAFLD, calling for further investigation and clinical testing.